Records analysis of the basking shark Cetorhinus maximus (chondrichthyes : lamniformes : lamnidae) in Tunisian coast (Central Mediterranean sea) - Ennajjar, Samira; Saidi, Bechir; Bradai, M. Nejmeddine (2019)
Investigations carried out along the Tunisian coasts for the study of the elasmobranch diversity since 1996 as well as bibliographic data revealed the record of fifteen basking shark. All individuals are caught accidentally at shallow depths. Gillnets and trammel nets are the gears responsible for most of these catches. 78% of the catches are males. Mature specimens (LT> 7m) represent only 20% of the total. Des investigations menées sur les côtes tunisiennes pour l’étude de la diversité des élasmobranches à partir de 1996 ainsi qu’une analyse bibliographique ont révélé la signalisation de quinze spécimens du requin pèlerin. Tous les individus sont pêchés accidentellement à des faibles profondeurs. Les filets maillants et trémails sont les engins responsables de la majorité de ces captures. 78% des captures sont des mâles. Les spécimens matures (LT>7m) ne représentent que 20% des prises. Published Refereed